Portulaca oleracea L. polysaccharide ameliorates lipopolysaccharide-induced inflammatory responses and barrier dysfunction in porcine intestinal epithelial monolayers. (April 2022) - Zhuang, Shen; Ming, Ke; Ma, Ning; Sun, Jinrui; Wang, Dehai; Ding, Mingxing; Ding, Yi
Graphical abstract: Abstract: Intestinal epithelial barrier and inflammatory responses are common pathological process in intestinal diseases. Effects of a specific polysaccharide fraction (POPZ ) from Portulaca oleracea L. on LPS-induced barrier injury and inflammatory responses were studied in porcine intestinal epithelial monolayer. POPZ was characterized by its molecular constituents with Man, GlcUA, Glc, Gal, Xyl and Fuc (0.247:0.245: 0.225: 0.179: 0.077:0.026, molar ratio), and Mp (41.496 kDa), Mw (51.418 kDa) and Mn (34.455 kDa). POPZ inhibited an increase in FD4 and phenol red permeability, and a decrease in TER and p-EGFR levels, and ZO-1, OCLN, claudin-7 and EGFR expression in LPS-treated porcine intestinal epithelial monolayer, which were counteracted by ZD1839, an EGFR inhibitor. It also ameliorated LPS-induced increase in IL-1β, IL-6, TNF-α, TLR4, NF-κB p-p65 and NF-κB p65 nuclear translocation. Taken together, POPz could relieve inflammatory responses and maintain the intestinal epithelial barrier via inactivating TLR4/NF-κB pathway and activating EGF/EGFR pathway.